2013
DOI: 10.2478/s13382-013-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Observance of hand washing procedures performed by the medical personnel after the patient contact. Part II

Abstract: Objectives: The Centers for Disease Control and Prevention (CDC) as well as the World Health Organization (WHO) state that adequate hand hygiene maintained by medical personnel is an indispensable prerequisite for controlling nosocomial infections. The recommendations of CDC and WHO emphasize the obligation to wash hands after each contact with a patient, after the exposure to a potentially infectious material or upon the contact with objects surrounding the patient. Materials and Methods: The study was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
(18 reference statements)
0
17
0
3
Order By: Relevance
“…W literaturze przedmiotu można znaleźć nieliczne polskie badania poświęcone praktyce higieny rąk przez pracowników medycznych [8][9][10]. Ich wyniki wskazują, że wciąż jest to obszar wymagający intensywnej edukacji oraz promocji właściwych postaw i zachowań.…”
Section: Materiał I Metodyunclassified
See 2 more Smart Citations
“…W literaturze przedmiotu można znaleźć nieliczne polskie badania poświęcone praktyce higieny rąk przez pracowników medycznych [8][9][10]. Ich wyniki wskazują, że wciąż jest to obszar wymagający intensywnej edukacji oraz promocji właściwych postaw i zachowań.…”
Section: Materiał I Metodyunclassified
“…Zarówno taka samoocena, jak i opinia o zgodności postępowania pracowników medycznych z zaleceniami są znacząco wyższe w porównaniu z wynikami badania obserwacyjnego Garus-Pakowskiej i wsp., którzy wykazali niepokojąco niskie odsetki zgodności, zależne od zawodu, miejsca świadczenia usług i sytuacji [8,9]. Badacze ci stwierdzili, że częściej pracownicy medyczni stosują się do zaleceń higieny rąk po kontakcie z pacjentem niż przed -odsetek zgodności śred-nio 26,4% vs 5,2%.…”
Section: Omówienieunclassified
See 1 more Smart Citation
“…Garus-Pakowska [6,7], in an observational study, found that in the situation prior to contact with the patient, only 16.8% of doctors and 4.7% of nurses performed hand hygiene according to the recommendations, and after contact these proportions were 53.1% and 25.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that hands were washed more frequently after contact with patients than before such contact [9,10], it once again becomes evident that hand hygiene, as an element of protection against infection, is regarded by the medical personnel as being more for their own protection than for the safety of the patients. The observed multiple use of disposable gloves evidently confirms that attitude.…”
Section: Ijomeh 2013;26(3) 427mentioning
confidence: 99%